Evaluated depressive symptoms in patients with hypothyroidism. - Spasovska Trajanovska, Aneta; Mitic, Zora; Pereska, Zhanina; Janicevic, Danijela (SHMSHM - AAMD, 2021)
Some studies show that a varying degree of psychiatric disorders is common in patients with Thyroid dysfunction. Both hypo and hyperthyroidism can cause mood abnormalities such as emotions and cognition. Depression can also go with thyroid dysfunction. Thyroid hormone has important actions in the adult brain they effect the site of raphe nuclei which probably results in an reduction the release of serotonin from raphe neurons. So assessment of the thyroid function test can be a good predictor in the treatment of depression disorders. The AIM of this study is to fine the prevalence of depressive symptoms among patients with hypothyroidism. Materials and methods: This cross-section present study included groups of 50 patients of either sex between 26-55 years with diagnosis hypothyroidism evaluated in Private Psychiatric Institution Zora Mitic, Skopje and Psychiatric Hospital Skopje. The study was conducted for 6 month. All the patients was written informed consent. Exclusion criteria was exist depressive disorders before being diagnosed as hypothyroidism, patients with another psychiatric disorders and another organic disorders. The patients were assess using the sociodemographic information by semi-structured questionnaire specially designed for the study. Depression in patients was assess by Back Depression Inventory scale: 21 items graded ranging 0-4 . The results obtained were compared using the Chi-square test and Spearman’s coefficient correlation. The quantitative data were expressed in number and percentage. Results: In this study only 20% of patients with hyperthyroidism have score of BDI >10. The total group of observations had significantly higher number of patients older then 36, unmarried, higher educated with increased BDI over 10, but there were no significant difference in patient’s location of living. Also we got that the BDI score were not statistically significant when compare males and females p=0,474. Conclusion: The correlation between psychiatry disorders and thyroid status is a major area of concern. So the patients mast be monitored and treating by both endocrinologist and a psychiatrist.
Keywords: hypothyroidism; depression; patients